Accuracy of self-assessment in gastrointestinal endoscopy: a systematic review and meta-analysis - Scaffidi, Michael A.; Li, Juana; Genis, Shai; Tipton, Elizabeth; Khan, Rishad; Pattni, Chandni; Gimpaya, Nikko; Bradley-Ridout, Glyneva; Walsh, Catharine M.; Grover, Samir C. (Endoscopy, 2022)
Background Assessment is necessary to ensure both attainment and maintenance of competency in gastrointestinal (GI) endoscopy, and this can be accomplished through self-assessment. We conducted a systematic review with meta-analysis to evaluate the accuracy of self-assessment among GI endoscopists. Methods This was an individual participant data meta-analysis of studies that investigated self-assessment of endoscopic competency. We performed a systematic search of the following databases: Ovid MEDLINE, Ovid EMBASE, Wiley Cochrane CENTRAL, and ProQuest Education Resources Information Center. We included studies if they were primary investigations of self-assessment accuracy in GI endoscopy that used statistical analyses to determine accuracy. We conducted a meta-analysis of studies using a limits of agreement (LoA) approach to meta-analysis of Bland–Altman studies.Results After removing duplicate entries, we screened 7138 records. After full-text review, we included 16 studies for qualitative analysis and three for meta-analysis. In the meta-analysis, we found that the LoA were wide (−41.0 % to 34.0 %) and beyond the clinically acceptable difference. Subgroup analyses found that both novice and intermediate endoscopists had wide LoA (−45.0 % to 35.1 % and −54.7 % to 46.5 %, respectively) and expert endoscopists had narrow LoA (−14.2 % to 21.4 %).Conclusions GI endoscopists are inaccurate in self-assessment of their endoscopic competency. Subgroup analyses demonstrated that novice and intermediate endoscopists were inaccurate, while expert endoscopists have accurate self-assessment. While we advise against the sole use of self-assessment among novice and intermediate endoscopists, expert endoscopists may wish to integrate it into their practice.